Penapisan Hiperuresemia dan Obesitas Pada Remaja di Jakarta Barat - Alexander Halim Santoso; Marcella E. Rumawas; David Limanan; Freddy Ciptono (Pusat Riset dan Inovasi Nasional, 2023)
Hyperuricemia is a pathophysiological condition associated with chronic inflammatory diseases such as rheumatoid arthritis, diabetes, and cardiovascular and kidney disease. Hyperuricemia is related to changes in lifestyle. Elevated serum uric acid levels can be a marker for the metabolic syndrome that commonly occurs in adults. Obesity is a complex condition involving biological, developmental, environmental, behavioral and genetic factors. The most common cause of obesity during adolescence is an imbalance in energy balance; i.e. excess caloric intake without appropriate caloric expenditure. Tomang sub-district is a sub-district under the Faculty of Medicine, Tarumanagara University. More than 25% of adults in the Tomang sub-district have hyperuricemia and 60% of the community are obese. So far it is not known how much the prevalence of hyperuricemia and obesity in adolescents in the Tomang Village. The promotion of healthy lifestyles and the prevention of disease are the fundamental principles behind public health and the promotion of public health. Measuring uric acid levels can prevent acute attacks of gout. The purpose of this service is to get an overview of the uric acid levels and obesity of the youth group in Tomang Village, West Jakarta